1991
DOI: 10.1002/gcc.2870030110
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 16 abnormalities associated with myeloid malignancies

Abstract: Twenty-six patients who had cytogenetic analyses performed for myeloid malignancies at St. Vincent's Hospital over a 6-year period were found to have an inversion abnormality of chromosome 16 (25 patients) or t(16;16) (1 patient). Only 16 patients had all the features of M4Eo, while the other 10 patients had diagnoses of M2, M4, M5, RAEB, and RAEB-T; six of these had abnormal eosinophils. Thus, abnormal eosinophils were present in 22 of 26 patients (85%). Thirteen patients had additional cytogenetic abnormalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 17 publications
0
18
1
Order By: Relevance
“…25 Comparisons of the CBF␤-MYH11/ABL ratios at diagnosis and relapse and during treatment and CR were performed by the Kruskal-Wallis test. 2 analysis was used for binary variables. All analyses were performed using the SPSS software package (SPSS, Chicago, IL).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Comparisons of the CBF␤-MYH11/ABL ratios at diagnosis and relapse and during treatment and CR were performed by the Kruskal-Wallis test. 2 analysis was used for binary variables. All analyses were performed using the SPSS software package (SPSS, Chicago, IL).…”
Section: Discussionmentioning
confidence: 99%
“…Forty-eight of the samples positive at real-time RT-PCR had been negative at qualitative RT-PCR using the BIOMED-1 Concerted Action protocol. 2 analysis revealed that real-time RT-PCR was significantly more sensitive (P Ͻ .001).…”
Section: Application Of Real-time Rt-pcr For Cbf␤-myh11 Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] The molecular marker is detectable by reverse transcription-polymerase chain reaction assay (RT-PCR) [5][6][7][8][9] on RNA at the time of diagnosis, and could be particularly useful for monitoring MRD in patients who achieve complete clinical remission (CCR) after induction therapy. [10][11][12][13] Marcucci et al 14 and several other authors [10][11][12][13] have reported favorable clinical outcomes despite persistence of CBF␤/MYH11 transcripts detected by RT-PCR; similar findings have been reported for another core-binding-factor altered in AML, 15,16 in which positive expression of AML1-ETO transcript can persist after induction and consolidation chemotherapy without evidence of hematological relapse.…”
Section: Molecular Remission In Pcr-positive Acute Myeloid Leukemia Pmentioning
confidence: 99%
“…However, the long-term survival is between 35 and 45%. 1,2 One of the possible explanations may be the infusion of tumor cells in the graft after high-dose chemotherapy. It has been shown that peripheral blood stem collections contain Hodgkin's cells.…”
Section: G Martinellimentioning
confidence: 99%